Investigation of influence of defectiveness in aluminous porcelain structure on fracture process under compressive loading using acoustic emission method - Ranachowski, Przemysław; Rejmund, Feliks; Pawełek, A.; Piątkowski, A. (Archives of Acoustics, 2006)
This work presents acoustic emission (AE) and microscopic study of ceramic samplessubjected to compressive stress. The object of research were specimens made of insulator aluminousporcelain 130 type. Purpose of this work was registration the stages of the processof degradation in ceramic material structure. Microscopic study allowed observing structuralparameters of material before loading and on particular stages of the process of defects development.Influence of technological faults existing in material structure on mechanical-acousticcharacteristics and mechanical strength of the samples was recognized.